Teach yourself visually MacBook Pro and MacBook Air - Hart-Davis, Guy (Teach yourself visually., 2020)
"Teach Yourself VISUALLY MacBook is your ultimate guide to getting up and running quickly with your new MacBook Pro or MacBook Air! Whether you're new to computers or transitioning from a PC, this graphics-heavy guide will show you everything you need to know to get the most out of your new laptop. Clear, step-by-step instructions walk you through each task, with screenshots that help you follow along with confidence. You'll learn how to manage files, work with macOS software, organize photos and media, set up email, access the internet, and adjust settings and preferences to make your MacBook work the way you work. You'll also explore the features that bring computing to a whole new level, including iCloud, FaceTime, the App Store, and so much more!"--Amazon.com.